From trust to skepticism: Has influencer marketing reached its breaking point? (Revista Română de Jurnalism și Comunicare, 2025)
Influencer marketing has become a mix of traditional endorsements and digital communication, initially praised for its authenticity and trustworthiness. However, increasing commercialization, saturation, and more critical consumer awareness are testing its effectiveness. While influencers still provide a more natural advertising alternative, issues like perceived inauthenticity, brand control, and declining trust are growing concerns. Authenticity, transparency, and credibility remain the key elements of successful influencer marketing. However, transparency can have paradoxical effects—boosting authenticity but possibly decreasing engagement if content seems too promotional. The type of influencer also matters: micro-influencers often build stronger trust because of perceived accessibility, while macro-influencers risk credibility due to overexposure and commercialization.This study analyzes two case studies. The first explores the 2023 “Pandoro Gate” scandal involving Chiara Ferragni, fined for misleading claims about charitable donations tied to product sales. The second focuses on Matilda Djerf, whose curated online image clashed with allegations of a toxic work environment. Both cases underscore the fragility of perceived authenticity and its implications for consumer trust.Findings suggest that influencer marketing is not in decline but at a pivotal moment. For long-term effectiveness, brands must embrace authenticity, prioritize value alignment, and grant influencers creative autonomy. Meaningful, transparent, and audience-aligned strategies are essential to maintain trust and relevance in an increasingly discerning digital landscape.